SYI'AH DAN SUNNI DALAM PERSPEKTIF PEMIKIRAN ISLAM - Abidin, Zainal (Hunafa: Jurnal Studia Islamika, 2006)
Shiite and Sunnite are two great Muslim groups emerging after the Prophet’s death. Shiite was considered a minor Muslim group who claimed that it was Ali ibn Abi Thalib who was eligible to a caliph (imam) after the Prophet’s death. Its reason was that Ali ibn Abi Thalib was the closet family of all Prophet’s companions. However, as a mayor Muslim group, Suniite claimed that all Prophet’s companions were eligible to a chaliph since the Prophet left no message to any of his copmpanions on who would be a chaliph after his death. It was this fact that aroused dispute on the chaliphate between the two Muslim groups. Kata Kunci: Syi’ah, Sunni, imamah, khilafah